2014
DOI: 10.1590/s1678-86212014000300009
|View full text |Cite
|
Sign up to set email alerts
|

Comparação das resistências ao embutimento paralelo às fibras de madeiras de pínus oocarpa, cumaru e pínus taeda

Abstract: A norma brasileira NBR 7190 (ABNT, 1997) estabelece as diretrizes para a determinação da resistência da madeira ao embutimento com pinos metálicos por meio de ensaios laboratoriais ou, na ausência deles, disponibiliza equações que permitem estimar a resistência da madeira ao embutimento. A referida norma admite ainda que na direção paralela às fibras da madeira a resistência à compressão seja igual à resistência ao embutimento. O objetivo deste trabalho consistiu em analisar as resistências de embutimento e de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
1
5
0
1
Order By: Relevance
“…Table 1 presents the average values of embedment strength (x m ), standard deviation (Sd), coefficient of variation (CV) and maximum (Max) and minimum (Min) values found from the Standard tests. Schizolobium amazonicum wood specie is classified as strength class C20 of dicotyledonous according to the Brazilian Standard Code ABNT NBR 7190:1997 [17,19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the average values of embedment strength (x m ), standard deviation (Sd), coefficient of variation (CV) and maximum (Max) and minimum (Min) values found from the Standard tests. Schizolobium amazonicum wood specie is classified as strength class C20 of dicotyledonous according to the Brazilian Standard Code ABNT NBR 7190:1997 [17,19].…”
Section: Methodsmentioning
confidence: 99%
“…Embedment parallel to grain strength is essential in evaluation of structural joints, but it's necessary to observe that some related problems can occur during procedures of nailing or bolting [11][12][13][14][15][16][17]. Molina et al [18] carried out tests to determine embedment strength of Pinus elliotti and Eucaliptus saligna.…”
Section: Introductionmentioning
confidence: 99%
“…The American and Brazilian Standards [2][3][4][5][6][7][8][9][10][11] have their specific equations for determining the embedment strength parallel and perpendicular to the grain, and these are listed in Table 1. [2][3][4][5][6][7][8][9][10][11] f e0 = 0.07725.…”
Section: Calculated Embedment Strenghtmentioning
confidence: 99%
“…The embedment of the steel dowel in the wood is characterized by the displacement of the joint towards a certain applied force. Contributions to the study of this phenomenon have been conducted for several researchers [5][6][7][8][9][10] to improve understanding of the timber structure joints. However, despite the growing interest in the study of timber structure joints in Brazil, it is observed that the investigations conducted so far have not produced enough conclusions for a correct analysis of timber structure joints behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation